Gauged thirring model in the Heisenberg picture - Lunardi, J. T. [UNESP]; Pimentel, D. M. [UNESP]; Manzoni, L. A. (My University, 2000)
We consider the (2+1)-dimensional gauged Thirring model in the Heisenberg picture. In this context we evaluate the vacuum polarization tensor as well as the corrected gauge boson propagator and address the issues of generation of mass and dynamics for the gauge boson (in the limits of QED 3 and Thirring model as a gauge theory, respectively) due to the radiative corrections.
Keywords: mass; mathematical model; polarization; quantum mechanics; review; vacuum